Undernutrition-induced substance metabolism and energy production disorders affected the structure and function of the pituitary gland in a pregnant sheep model - Liu, Shuai; Lu, Huizhen; Mao, Shengyong; Zhang, Zijun; Zhu, Wen; Cheng, Jianbo; Xue, Yanfeng (Frontiers in Nutrition, 2023)
Undernutrition spontaneously occurs for ewes during late gestation and pituitary is an important hinge in neurohumoral regulatory system. However, little knowledge is known about the effect of undernutrition on pituitary metabolism. Here, 10 multiparous ewes during late gestation were restricted to 30% feeding level to establish an undernutrition model while another 10 ewes were fed normally as controls. All the ewes were sacrificed and pituitary samples were collected to perform transcriptome, metabolome, and quantitative real-time PCR analysis and investigate the metabolic changes. PCA and PLS-DA of total genes showed that undernutrition changed the total transcriptome profile of pituitary gland, and 581 differentially expressed genes (DEGs) were identified between the two groups. Clusters of orthologous groups for eukaryotic complete genomes demonstrated that substance transport and metabolism including lipid, carbohydrate, and amino acid, energy production and conversion, ribosomal structure and biogenesis, and cytoskeleton were enriched by DEGs.Kyoto encyclopedia of genes and genomes pathway enrichment analysis displayed that phagosome, intestinal immune network, and oxidative phosphorylation were enriched by DEGs. Further analysis found that undernutrition enhanced the lipid degradation and amino acid transport, repressing lipid synthesis and transport and amino acid degradation of the pituitary gland. Moreover, the general metabolic profiles and metabolic pathways was affected by undernutrition with repressed the 60S, 40S, 28S, and 39S subunits of ribosomal structure for translation and myosin and actin synthesis for cytoskeleton. Undernutrition was found also to be implicated into suppression of the oxidative phosphorylation for energy production and conversion, into a downregulation of genes related to T cell function and immune response and an upregulation of genes involved in inflammatory reaction enriching in phagosome. This study comprehensively analyzes the effect of undernutrition on pituitary gland in a pregnant sheep model, which provides a foundation for further mechanisms research on undernutrition caused hormone secretion and metabolic disorders.